Anti-viral activity of red microalgal polysaccharides against retroviruses - Talyshinsky, Marina M (BioMed Central, 2002)
Red microalgal polysaccharides significantly inhibited the production of retroviruses (murine leukemia virus- MuLV) and cell transformation by murine sarcoma virus(MuSV-124) in cell culture. The most effective inhibitory effect of these polysaccharides against both cell transformation and virus production was obtained when the polysaccharide was added 2 h before or at the time of infection. Although, addition of the polysaccharide post-infection significantly reduced the number of transformed cells, but its effect was less marked than that obtained when the polysaccharide was added before or at the time of infection.The finding that the inhibition of cell transformation by MuSV-124 was reversible after removal of the polysaccharide suggested that microalgal polysaccharides inhibited a late step after provirus integration into the host genome. In conclusion, our findings could support the possibility that the polysaccharide may affect early steps in the virus replication cycle, such as virus absorption into the host cells, in addition to its effect on a late step after provirus integration.